An evolving approach to unconferencing: Reflections from piloting the HELTASAFEST22 scholarly festival - Krull, Greig; Bobo, Benita; Titus, Simone (Critical Studies in Teaching and Learning, 2024)
This article offers insight into the planning and facilitation of a scholarly learning and teaching festival which aims to negotiate the tensions between traditional and creative scholarly engagements in the Southern African higher education context. The aim of this case study is to critically reflect on planning and facilitating a scholarly learning and teaching festival as part of an (un)conferencing approach for HELTASA. The case study adopts a critical reflective methodology, where we reflect on our experiences and perceptions of planning and facilitating/participating in the festival. The article outlines the structure and methodologies of the festival and reflects on the contextual considerations for planning the festival and the positives and challenges associated with facilitating the festival. A major tension that had to be managed as part of the festival was the questions of academic rigour and the choice of a festival by some prospective participants.